Single-Cell RNA Sequencing Unravels Upregulation of Immune Cell Crosstalk in Relapsed Pediatric Ependymoma - Wu, Haoda; Fu, Ruiqing; Zhang, Yu-Hong; Liu, Zhiming; Chen, Zhen-Hua; Xu, Jingkai; Tian, Yongji; Jin, Wenfei; Wong, Samuel Zheng Hao; Wu, Qing-Feng (Frontiers in Immunology, 2022)
Ependymoma (EPN) is a malignant glial tumor occurring throughout central nervous system, which commonly presents in children. Although recent studies have characterized EPN samples at both the bulk and single-cell level, intratumoral heterogeneity across subclones remains a confounding factor that impedes understanding of EPN biology. In this study, we generated a high-resolution single-cell dataset of pediatric ependymoma with a particular focus on the comparison of subclone differences within tumors and showed upregulation of cilium-associated genes in more highly differentiated subclone populations. As a proxy to traditional pseudotime analysis, we applied a novel trajectory scoring method to reveal cellular compositions associated with poor survival outcomes across primary and relapsed patients. Furthermore, we identified putative cell–cell communication features between relapsed and primary samples and showed upregulation of pathways associated with immune cell crosstalk. Our results revealed both inter- and intratumoral heterogeneity in EPN and provided a framework for studying transcriptomic signatures of individual subclones at single-cell resolution.